High voltage Mg-doped Na0.67Ni0.3xMgxMn0.7O2 (x = 0.05, 0.1) Na-ion cathodes with enhanced stability and rate capability - Singh, G; Tapia-Ruiz, N; Lopez del Amo, J; Maitra, U; Somerville, J; Armstrong, A; Martinez de Ilarduya, J; Rojo, T; Bruce, P (American Chemical Society, 2016)
Magnesium substituted P2-structure Na0.67Ni0.3Mn0.7O2 materials have been prepared by a facile solid-state method and investigated as cathodes in sodium-ion batteries. The Mg-doped materials described here were characterised by X-ray diffraction (XRD), 23Na solid-state nuclear magnetic resonance (SS-NMR) and scanning electron microscopy (SEM). The electrochemical performance of the samples was tested in half cells vs. Na metal at room temperature. The Mg-doped materials operate at a high average voltage of ca. 3.3 V vs. Na/Na+ delivering specific capacities of ~ 120 mAh g-1 which remain stable up to 50 cycles. Mg doping stabilizes the structure in the high voltage region by suppressing the well-known P2-O2 phase transition observed in the pristine composition. Instead, an OP4 phase was observed during charging (during Na removal) of the Mg-doped materials. GITT measurements showed that the Na-ion mobility is improved by two orders of magnitude with respect to the parent P2 Na0.67Ni0.3Mn0.7O2. The fast Na-ion mobility may be the cause of the good observed rate performance.